Samuel Richardson and the art of letter-writing - Curran, Louise (Cambridge University Press, 2018)
"This fascinating study examines Samuel Richardson's letters as important works of authorial self-fashioning. It analyses the development of his epistolary style; the links between his own letter-writing practice and that of his fictional protagonists; how his correspondence is highly conscious of the spectrum of publicity; and how he constructed his letter collections to form an epistolary archive for posterity. Looking backwards to earlier epistolary traditions, and forwards, to the emergence of the lives-in-letters mode of biography, the book places Richardson's correspondence in a historical continuum. It explores how the eighteenth century witnesses a transition, from a period in which an author would rarely preserve personal papers to a society in which the personal lives of writers become privileged as markers of authenticity in the expanded print market. It argues that Richardson's letters are shaped by this shifting relationship between correspondence and publicity in the mid-eighteenth century"...
Includes bibliographical references and index
Keywords: Richardson, Samuel -- 1689-1761 -- Criticism and interpretation; Richardson, Samuel -- 1689-1761 -- Correspondence; Richardson, Samuel -- 1689-1761 -- Friends and associates; Richardson, Samuel -- 1689-1761; Geschichte 1700-1800; Geschichte; Gesellschaft; Authors, English -- 18th century -- Correspondence; English letters -- 18th century -- History and criticism; Letter writing -- England -- History -- 18th century; Letter writing -- Social aspects -- England; Autobiography -- Social aspects; Brief; Hochschulschrift